1993
DOI: 10.1021/bc00024a015
|View full text |Cite
|
Sign up to set email alerts
|

(6-Maleimidocaproyl)hydrazone of doxorubicin. A new derivative for the preparation of immunoconjugates of doxorubicin

Abstract: The (6-maleimidocaproyl)hydrazone of doxorubicin was synthesized and conjugated to several mAbs, including chimeric BR96, via a Michael addition reaction to thiol-containing mAbs. DTT reduction of disulfides present in the mAb was a reliable and general method for generating a consistent number of reactive SH groups. The conjugates, after purification by Bio-Beads, were free of unreacted linker and/or doxorubicin. All conjugates released doxorubicin under acidic conditions that mimic the lysosomal environment,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
170
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 212 publications
(176 citation statements)
references
References 24 publications
(37 reference statements)
4
170
0
Order By: Relevance
“…IgG1 molecules contain 12 intrachain and 4 interchain disulfide bonds. However, it has been shown that the latter are significantly more susceptible to reduction by agents such as DTT than are the intrachain bonds (27,28). In fact, Willner et al (27) reported that reduction of a chimeric antibody with up to 100 molar equivalents of DTT could only generate eight sulfhydryls per antibody corresponding to reduction of the four interchain disulfide bonds.…”
Section: Discussionmentioning
confidence: 99%
“…IgG1 molecules contain 12 intrachain and 4 interchain disulfide bonds. However, it has been shown that the latter are significantly more susceptible to reduction by agents such as DTT than are the intrachain bonds (27,28). In fact, Willner et al (27) reported that reduction of a chimeric antibody with up to 100 molar equivalents of DTT could only generate eight sulfhydryls per antibody corresponding to reduction of the four interchain disulfide bonds.…”
Section: Discussionmentioning
confidence: 99%
“…The resulting mixture was sonicated few minutes until complete dissolution. [6-(maleimido)hexanamido]azanium trifluoroacetate (7) [23] (0.306 g, 0.868 mmol) and 4 Å molecular sieves (200 mg) were then added and the reaction mixture was stirred for 1 h at room temperature under nitrogen. The formation of the desired product (9) was monitored by TLC (petroleum ether/ethyl acetate 1/1 v/v, R f : 0.65).…”
Section: Synthesis and Characterization Of 6-(maleimidyl)-hexanoic Acmentioning
confidence: 99%
“…Doxorubicin conjugated to mAb cBR96, by using a thiol linker to the mAb and acid-labile hydrazone linker to the drug, was produced as previously described, 11 to yield a molar ratio of 8 drugs per mAb. [Methyl 3 H]-thymidine was purchased from Amersham (Piscataway, NJ).…”
Section: Reagentsmentioning
confidence: 99%
“…Following binding to the Le y tumor antigen, cBR96-Dox is internalized via endocytosis, the hydrazone linkage of mAb to drug is cleaved within the acidic environment of the endocytic vesicle and free doxorubicin is released into the cytosol. 8,11 To examine the contribution of internalization to sensitivity, the rates of cBR96-Dox uptake, surface levels of Le y antigen and IC 50 for the conjugate were compared on four different Le y -positive tumor lines ( Fig. 1).…”
Section: Antigen Internalization Provides Sensitivity To Cbr96-doxmentioning
confidence: 99%
See 1 more Smart Citation